HUBUNGAN UMUR, BEBAN KERJA DAN POSISI DUDUK SAAT BEKERJA DENGAN KELUHAN NYERI PUNGGUNG PADA PENGEMUDI ANGKUTAN KOTA DI KABUPATEN WONOSOBO JAWA TENGAH - Fitriningsih, .; Hariyono, Widodo (Universitas Ahmad Dahlan, 2011)
Background: Wonosobo station lies in Wonosobo Regency, Central Java, Association of Driver of Wonosobo-Sawangan City Transportation (PERKASA) is an organization which serve the transportation needs of Wonosobo people. It has 80 buses with 60 drivers. Method: this study is an analytic observational study with a cross sectional design on drivers of city transportation in Wonosobo. The study aims to identifying the relationship between the age, working load, and sitting position when having a job and complain on back. The applied instrument is a checklist based on the adoption from Nilamsari?s study with 33 respondents who meet the inclusive criteria. Result: most the age of drivers in the risk category of positive backache, 17 people (51.5%). While the age of drivers without the risk of negative backache is 5 people (15.3%). The respondents? working load in the light category with negative backache is 14 people (42.4) and with positive backache are 17 people (51.5%. The sitting position of the respondent in the unsuitable category with the negative backache is 12 people (36%) and with the positive backache are 18 people (45.5%). While the sitting position of respondents is less suitable with negative backache is 3 people (9.1%) and nobody feel positive backache. Conclusion: There is a relationship in the year between age and sitting position when having a job with complain of backache in driver relationship city transportation in the year 2010. Keyword: age, working load, sitting position and load back.